WOMEN’S PARTICIPATION IN LOCAL GOVERNANCE IN MUARA ENIM REGENCY - Muhamad Uyun; Ike Utia Ningsih; Zata Ismah; Indah Nurisa; Yulia Fitria; Royda fauzi (EGALITA, 2025)
Abstract Women’s participation in local government is a crucial indicator of inclusive and gender-equitable development. This study aims to analyze the roles and participation of women within the bureaucratic structure of Muara Enim Regency, as well as the enabling and constraining factors influencing their involvement in public policy decision-making. A descriptive qualitative approach was employed using literature review, policy document analysis, questionnaires, and interviews with female civil servants in local government institutions. The findings reveal that women’s representation in strategic bureaucratic positions remains limited despite the presence of national and regional affirmative action policies. Structural constraints such as patriarchal culture, gender stereotypes, and restricted access to leadership training continue to impede women’s advancement. Conversely, affirmative regulations, increasing levels of women’s education, and strong social networks serve as key enabling factors. The study emphasizes the need to strengthen gender-responsive regional policies, expand leadership capacity-building for female civil servants, and cultivate an inclusive bureaucratic environment. These findings are expected to contribute as policy references for local governments and gender advocates in promoting women’s roles in equality-oriented development. Keywords: Women’s participation; Local Government; Gender Equality; Public Policy Abstrak Partisipasi perempuan dalam pemerintahan daerah merupakan indikator penting dalam mewujudkan pembangunan yang inklusif dan berkeadilan gender. Penelitian ini bertujuan untuk menganalisis peran dan tingkat keterlibatan perempuan dalam struktur birokrasi Pemerintah Kabupaten Muara Enim serta mengidentifikasi faktor pendorong dan penghambat yang memengaruhi partisipasi mereka dalam pengambilan keputusan kebijakan publik. Pendekatan kualitatif deskriptif digunakan melalui kajian literatur, analisis dokumen kebijakan daerah, kuesioner, dan wawancara dengan aparatur sipil negara (ASN) perempuan di lingkungan pemerintahan daerah. Temuan penelitian menunjukkan bahwa representasi perempuan dalam posisi strategis masih terbatas meskipun telah tersedia kebijakan afirmatif di tingkat nasional dan daerah. Hambatan struktural seperti budaya patriarki, stereotip gender, dan akses terbatas terhadap pelatihan kepemimpinan menjadi tantangan utama. Sebaliknya, kebijakan afirmatif, peningkatan tingkat pendidikan perempuan, dan keberadaan jaringan sosial yang kuat menjadi faktor pendorong yang signifikan. Penelitian ini menekankan pentingnya penguatan regulasi daerah yang responsif gender, penyediaan pelatihan kepemimpinan bagi ASN perempuan, serta pembangunan ekosistem birokrasi yang lebih inklusif. Temuan ini diharapkan dapat menjadi rujukan kebijakan bagi pemerintah daerah dan para pegiat gender dalam mendorong peran perempuan dalam pembangunan berbasis kesetaraan. Kata Kunci: Partisipasi Perempuan; Pemrintahan Daerah; Kesetaraan Gender; Kebijakan Publik